A study of consumer preferences for traditional handicraft products of the Sanjiang Dong ethnic group: an interview method perspective - Liang Xianfei; Zairul Anuar Md. Dawam (Akademi Seni dan Teknologi Kreatif, Universiti Malaysia Sabah, 2024)
This study aims to explore consumer preferences for traditional handicraft products of the Dong ethnic group in Sanjiang, and to find out consumers' satisfaction with demand, popularity, opinions on improvement, and expectations of the products through qualitative research methods using face-to-face informal interviews. The results of the study show that consumers recognise the cultural attributes and exquisite craftsmanship of existing products, prefer diverse and portable creative products, want to incorporate Dong cultural symbols into modern commonly used artefacts, highlight the cultural and educational functions of the products, and have high expectations for experiential and customised services. Based on this, it is recommended to improve the craftsmanship of craftsmen, increase the diversity and creativity of product types, enhance product quality and cultural added value, clarify branding strategies, and develop small and practical products to meet modern market demands.